Seleção de bactérias láticas do kefir como produtoras de substâncias inibitórias de Listeria monocytogenes - Ligia Isoni Auad (2014)
Kefir is a sour fermented milk that contains a mixture of microrganisms, mainly lactic acid bacteria (LAB). LAB may be a useful and effective strategy to prevent or reduce the incidence of pathogens, thus improving food safety and consumer health. Strains of LAB isolated from kefir grains and identified by PCR were evaluated for their inhibitory activity against four strains of Listeria monocytogenes. The strains (n = 24) belonging to the genera Lactobacillus, Lactococcus and Leuconostoc were reciprocally tested by spot-on-lawn method and Lactobacillus satsumensis 18P was selected as the most sensitive strain. Twelve LAB strains that showed the highest inhibitory activity were then selected from which were obtained cell free supernatants (CFS) and cell free neutralized supernatants (CFNS) after cultivation in MRS broth. These supernatants were evaluated for their activity and inhibitory effect against strains of Listeria monocytogenes by the well diffusion and microtiter plates assays. CFS and CFNS tested by well diffusion assay showed no inhibition against Listeria monocytogenes. However, in the microtiter plate assay, growth inhibition of Listeria monocytogenes until 30 hours of incubation could be observed. From the CFS and CFNS tested, Leuconostoc mesenteroides 9U2 presented the best antagonistic effects. Thus, it can be concluded that the strains of LAB isolated from kefir have the ability of producing substances that are capable of inhibiting Listeria monocytogenes. These results are promising, since the supernatants tested showed such capacity in its crude form. Future studies should investigate the possibility of obtaining concentrates of these substances with the highest inhibitory potential and possible use in foods to ensure safety.